PENGELOLAAN LINGKUNGAN DARI ASPEK PENANGANAN SAMPAH DAN PEMANTAUAN LINGKUNGAN DENGAN BIOINDIKATOR SERANGGA LALAT DI KAWASAN WISATA PANTAI GEDAMBAAN KOTABARU - Satriansyah Satriansyah; Emmy Sri Mahreda; Abdul Ghofur; Jumar Jumar (Universitas Lambung Mangkurat, 2011)
GedambaanBeachlocated on Jl. Berangas Km. 14 Kabupaten Kotabaru is one of coastal tourism objects in South Kalimantan. Which is rich of coastal potential as tourism attraction. Based on experience and pre-observation on environment management activity in several coastal tourism object the result appeared differently, especialy in waste treatment becauase there were waste production rising in some particular spots that occurred in less good management system. Considering the importance of mangrove ecosystem existence in coastal area and inclination of polution cases in the area that mostly caused by the waste, it is needed to get describtion about waste treatment methode in tourism object that included in coastal resources use. Therefore the objective of this research is to know the factors that influence the waste management around the tourism object which are 1) Supporting factors, 2) Number of waste Production and waste volume, 3) Waste sort and waste compocition, 4) Waste reduction and waste treatment, 5) To know the environment condition around the tourism object by measuring the fly density. The observation (during May until July 2011) on environment management that related to waste management and environment observation by measuring the fly density in the area should that 1) Supporting factors consist of organization, personal, tools, and budged, 2) Waste production number and waste volume are depend on the number of visitors (128 – 342 individuals perday) and climated change. The measurement of waste volume in sevent days stretched obout 1.2 – 3.2 m3 perday or 2.1 m3 perday in average, 3) Waste sort and waste compocition ; organic waste such as dry leafes and coconut shells in more frekuently found (8.7 m3) than non-organic waste such as plastics, allumunium cans, bottles and mixed waste from the sea (4.4 m3), 4) Waste reduction and waste treatment ; they were no effort to reduce waste and doing waste treatment. The waste sorting were done only on coconut shell, and the last step would be burning down the waste. The conclusion of environment observation with fly as bioindacator are 1) There is relation beetwen fly density and the waste treatment. Chi-square statistic test result should that X2 measurment (9.97) is higher than X2 table (3.84), thus rejected Ho. That stated that “There are no relation beetwen fly density and waste treatment”, 2) The fly density (3.4 – 5.2) interpreted as moderate density, 3) The fly density index ( 3.4 – 5.2 ≤ 6 ) is considered as low therefore the environment management is consider good.